Occasional Tillage in a Wheat-Sorghum-Fallow Rotation - A. Schlegel; J. Holman (Kansas Agricultural Experiment Station Research Reports, 2020)
Beginning in 2012, research was conducted in Garden City and Tribune, KS, to determine the effect of a single tillage operation every 3 years on grain yields in a wheat-sorghum-fallow (WSF) rotation. Grain yields of wheat and grain sorghum were generally not affected by a single tillage operation every 3 years in a WSF rotation. Grain yield varied greatly by year from 2014 to 2019. Wheat yields ranged across years from mid-20s to 90 bu/a at Tribune and less than 10 to near 100 bu/a at Garden City. Grain sorghum yields ranged from 40 to greater than 140 bu/a, depending upon year and location. In 2019, wheat yields at Garden City were less when tillage was implemented post-wheat in 2016. There were no other years or locations were grain yields were significantly affected by a single tillage operation. However, at Tribune, when averaged across the 6-year period, a single tillage after wheat harvest reduced grain sorghum yields compared to a complete no-till (NT) system. At Garden City, averaged across the 6-year period, wheat yields were greatest following a one-time tillage prior to wheat. This indicates that if a single tillage operation is needed to control troublesome weeds, tillage during fallow prior to wheat planting may be better than tillage after wheat harvest. Furthermore, if herbicide-resistant weed populations were high enough to cause yield reductions, then tillage might improve yields.
Keywords: No-till; herbicide resistant weeds; crop rotation